Oxidation and property evolution of AISI T5 steel under varying heat treatments - DADOU , Abdenour; DILMI , Hamid; BEZZAZI , Boudjema; ARIBI, Chouaib; DAOUD , Ismail (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
This study evaluates the effect of heat treatment on the mechanical, tribological, and oxidation behavior of AISI T5 steel. The chemical composition was first characterized using spectroscopy and SEM. A two-year oxidation test conducted in humid and relatively dry atmospheres showed strong environmental sensitivity: in humid air, the oxidation rate reached 11.27×10-2 P/P0 per month with a sharp increase after 25 days, whereas in dry air it remained below1.35×10-2 P/P0 per month, following a linear and nearly flat trend indicative of a protective oxide scale.Heat treatment significantly increased hardness from 34.15 ± 0.59 HRC (untreated) to 62.70 ± 0.66 and 60.80 ± 0.48 HRC for water and oil quenched steels, respectively. Impact strength decreased accordingly, with oil quenching offering the best hardness-toughness balance (60.8 HRC, 2.08 Kcv). Instrumented indentation confirmed substantial surface strengthening, with HIT rising to 17.39 ± 0.29 GPa (Q. Water) and 7.68 ± 0.12 GPa (Q. Oil). Under dry sliding, wear rates were reduced by 81.3% (Q. Water) and 62.5% (Q. Oil), with faster run-in in the water-quenched condition. XRD revealed tempered martensite with Fe3W3C/Cr7C3 (Q. Water) and Co3W3C (Q. Oil), consistent with thermal conditions. This study provides new experimental data on the effects of 15-minute austenitization followed by oil or water quenching on the properties of AISI T5 steel, highlighting its potential for process optimization.
Keywords: AISI T5; Oxidation; Heat treatment; Hardness; Nanoindentation; Abrasion